Functional Distinction Between Visuomovement and Movement Neurons in Macaque Frontal Eye Field During Saccade Countermanding - Ray, Supriya (American Physiological Society, 2009)
In the previous studies on the neural control of saccade initiation using the countermanding paradigm, movement and visuomovement neurons in the frontal eye field were grouped as movement-related neurons. The activity of both types of neurons was modulated when a saccade was inhibited in response to a stop signal, and this modulation occurred early enough to contribute to the control of the saccade initiation. We now report a functional difference between these two classes of neurons when saccades are produced. Movement neurons exhibited a progressive accumulation of discharge rate following target presentation that triggered a saccade when it reached a threshold. When saccades were inhibited with lower probability in response to a stop signal appearing at longer delays, this accumulating activity was interrupted at levels progressively closer to the threshold. In contrast, visuomovement neurons exhibited a maintained elevated discharge rate following target presentation that was followed by a further enhancement immediately before the saccade initiation. When saccades were inhibited in response to a stop signal, the late enhancement was absent and the maintained activity decayed regardless of stop-signal delay. These results demonstrate that the activity of movement neurons realizes the progressive commitment to the saccade initiation modeled by the activation of the go unit in computational models of countermanding performance. The lack of correspondence of the activity of visuomovement neurons with any elements of these models indicates that visuomovement neurons perform a function other than the saccade preparation such as a corollary discharge to update visual processing.